STUDENT ATTITUDES OF SMA KOSGORO BANDAR SRIBHAWONO TOWARD THE JUVENILE CRIME CASES - umi farida; Adelina Hasyim; Hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
This research was aimed to explain the knowledges, feelings, and responses of SMA Kosgoro Bandar Sribhawono students related to phenomena youth crime cases. This research used descriptive research method with 31 respondents as the sample. The principal techniques of data collecting used questionnaires. To analyze the collected data used Percentage technique. The results of this research showed that the level of knowledge of respondents toward the youth crime cases are well, based on the percentage of 29 respondents (93.5%). Meanwhile respondent's feelings toward youth crime cases are not like/unfavorable based on the percentage of 24respondents (77.4%), and the students' response to youth crime cases are neutral, this is shown by the percentage of 16 respondents (51.6%). Meanwhile general attitude of students towards juvenile crime cases are not support, based on the percentage of 80.6% or 25 of the 31 students who were respondents. Based on the consideration that the deeds / actions / violation was an act that are prohibited by public law or penal law.Key Word : Student Attitudes, Crime Cases.